2016
DOI: 10.1016/j.compstruct.2015.11.065
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the influence of tool wear and special cutting geometry when drilling woven CFRPs

Abstract: CFRPs drilling is a common process in the aerospace industry carried out prior to components assembly. Machining induced damage leads to significant percentage of component rejection. Damage extension strongly depends on drilling geometry and cutting parameters. Fresh drill geometry changes with cutting time due to the wear progression and the risk for hole quality is enhanced as cutting progresses. The influence of wear on hole quality has been analyzed in the literature using mainly an experimental approach.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 32 publications
0
31
0
2
Order By: Relevance
“…Abrão et al [57] showed that 56% of the tools used for drilling polymer composites have a special geometry. Some of the special drilling tools developed for CFRP cutting are as follows: (i) double point angle twist drills [58][59][60][61][62][63][64], (ii) brad and spur drills [21,[65][66][67][68][69][70], (iii) dagger drills (one-shot drills) [28,31,[67][68][69][70][71][72][73], (iv) step drills [67,68,[74][75][76][77][78][79][80], (v) core drills [81,82] and (vi) special core drills [83][84][85]. These special drilling tools are reviewed and discussed in detail by Geier et al [55].…”
Section: Conventional Drilling and Helical Milling Of Cfrpsmentioning
confidence: 99%
“…Abrão et al [57] showed that 56% of the tools used for drilling polymer composites have a special geometry. Some of the special drilling tools developed for CFRP cutting are as follows: (i) double point angle twist drills [58][59][60][61][62][63][64], (ii) brad and spur drills [21,[65][66][67][68][69][70], (iii) dagger drills (one-shot drills) [28,31,[67][68][69][70][71][72][73], (iv) step drills [67,68,[74][75][76][77][78][79][80], (v) core drills [81,82] and (vi) special core drills [83][84][85]. These special drilling tools are reviewed and discussed in detail by Geier et al [55].…”
Section: Conventional Drilling and Helical Milling Of Cfrpsmentioning
confidence: 99%
“…Bu durum kompozit malzemelerin özgül kesme dirençlerinin düşük olmasına bağlıdır. Karbon fiber takviyeli kompozit malzemeler işlenirken kesme kuvvetlerinin düşük çıkması literatürle örtüşen bir durumdur [23,24]. Şekil 7'deki grafik incelendiğinde kesme hızındaki artış genel olarak kesme kuvvetlerinin düşmesine sebep olmuştur.…”
Section: Kesme Kuvvetlerinin Değerlendirilmesi (Evaluation Of Cuttingunclassified
“…At the same time, the high costs associated with experimental tests are reduced. However, many numerical models found in the literature have been developed to simulate machining processes, which involve rotary cutting movements, such as turning [17,18] or drilling [19]. In these cases, it is difficult to obtain experimental information about the effect of the orientation of the fibers on the tool and on the workpiece, so the differences between the experimental test and the conditions considered in the model definition reduce the precision of the model.…”
Section: Introductionmentioning
confidence: 99%